Growing on the Margins: Global Christian Higher Education - Glanzer, Perry L. (International Higher Education, 2017)
The more than 1,000 universities that identify a Christian identity globally are a growing global phenomenon. These universities are an especially rapidly growing segment of private higher education worldwide.